Beneficial Effects of Adrenal Androgen Supplement in Bleeding Cirrhotic Rats. Issue 6 (December 2018) - Huang, Hui-Chun; Hsu, Shao-Jung; Chang, Ching-Chih; Tsai, Ming-Hung; Lee, Fa-Yauh; Hou, Ming-Chih; Lee, Shou-Dong
Abstract : ABSTRACT: Critical illness is accompanied by hypothalamic-pituitary-adrenal axis activation, but adrenal insufficiency characterized by inadequate glucocorticoid synthesis is common in critically ill cirrhotic patients, the "hepato-adrenal syndrome." Adrenal cortex also synthesizes androgen (dehydroepiandrosterone, DHEA). DHEA maintains microcirculation by enhancing vascular endothelial nitric oxide synthase (eNOS) activity. In critical patients of other disease entities, a shift of adrenal steroidogenesis away from androgens toward glucocorticoid has been noted, arousing interests in androgen replacement in critical settings. Nevertheless, this has not been surveyed in cirrhosis with hemorrhage. In this study, liver cirrhosis was induced with common bile duct ligation (BDL) in Spraque-Dawley rats. Sham rats were controls. DHEA or vehicle was injected at the beginning of hemorrhage-transfused procedure, followed by terlipressin injection. Hemodynamic parameters were measured. Then abdominal aorta, superior mesenteric arteries (SMA) and splenorenal shunt (prominent portosystemic collateral vessel in rodents) eNOS and inducible NOS protein expressions were evaluated. In bleeding BDL groups without terlipressin injection, adrenocorticotropic hormone (ACTH) stimulation test was performed to evaluate the DHEA response. The results showed that DHEA significantly elevated mean arterial pressure, cardiac output, and stroke volume of bleeding cirrhotic rats treated with terlipressin and reduced systemic vascular resistance without affecting SMA flow, resistance, and portal pressure. DHEA upregulated abdominal aorta and SMA eNOS expressions. ACTH did not stimulate DHEA synthesis in bleeding BDL rats. In conclusion, androgen deficiency exists in bleeding cirrhotic rats. DHEA augments terlipressin-induced amelioration of shock without influencing splanchnic hemodynamics, possibly rendering it a feasible adjunct to vasoconstrictors in variceal hemorrhage.